MENUMBUHKAN SPIRITUALITAS MELALUI PUASA SENIN KAMIS: Studi Fenomenologi Santri Pondok Pesantren Annuqayah Daerah Lubangsa Putra - Hermanto; Matroni (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
Monday Thursday fasting is one of the sunnah worships, while students are one of the groups who are considered very devout in worship. At the Annuqayah Islamic Boarding School in the Lubangsa Putra area. The phenomenon of students who fast on Mondays and Thursdays is commonplace. Although it is not actually recommended and obligatory in Islamic Boarding Schools. Monday Thursday fasting is a sunnah worship recommended by the Prophet Muhammad saw., because of the benefits and advantages for those who practice it. One of the benefits of Monday Thursday fasting makes its practitioners peaceful people and can feel what the poor feel, and people who do not have food. So that fasting becomes one part of Islamic religious worship because fasting is riyaḍah or practice of leaving bad things to get closer to Allah Swt. This study aims to reveal two things: First, what is the spiritual motivation for undergoing Monday Thursday fasting for students at the Annuqayah Islamic Boarding School in the Lubangsa Putra area. Second, what is the spiritual impact of Monday Thursday fasting felt by students at the Annuqayah Islamic Boarding School in the Lubangsa Putra area. The author is based on the phenomenological method with Sigmund Freud's psychoanalytic theory regarding the drive of a person's behavior, and Imam al-Ghazali's Sufism regarding the spiritual level of people who fast to the spiritual experience of people who fast on Mondays and Thursdays. This study produces two conclusions that First, Feeling the spiritual motivation felt by students starting from intrinsic motivation, because of the desire from within, as well as a strong will to fast, and extrinsic motivation such as from the environment, and family which drives their spiritual motivation. Second, According to the experience felt by students who fast on Mondays and Thursdays, it can make spirituality within them grow in getting closer to Allah Swt.